Laravel Blade Templating Engine Implementation (Case Study: Muhammadiyah Lamongan Hospital Job Management System) - Wijayanto, Danur; Firmansyah, Firmansyah (Institut Teknologi Dirgantara Adisutjipto, 2022)
Laravel is one of several frameworks owned by the Hypertext Preprocessor (PHP) programming language. Laravel itself was created to facilitate programmers in creating a website with a framework that laravel is expressive and has syntax that is easy to understand. Laravel can also automate common things that are commonly used when building an application such as: Database library, Templating Engine, Session Management, etc. So much used to create a web application. Hypertext Markup Language (HTML), Cascading Style Sheets (CSS) and PHP programming languages: Hypertext Preprocessor is the most widely used programming language for creating a web sistem, using the Blade Templating Engine feature in the Laravel Framework will make it easier for programmers to create dynamic interfaces where programmers do not need to repeat the same code on each page, like; Navbar, Sidebar, footer and so on. By using directive yield, section and extends to call the template that has been created.